Linkage of voluntary medical male circumcision clients to adolescent sexual and reproductive health (ASRH) services through Smart-LyncAges project in Zimbabwe: a cohort study. Issue 5 (4th May 2020) - Makoni, Talent M; Thekkur, Pruthu; Takarinda, Kudakwashe C; Xaba, Sinokuthemba; Ncube, Getrude; Zwangobani, Nonhlahla; Samuelson, Julia; Mangombe, Aveneni; Mabaya, Simbarashe; Tapera, Talent; Matambo, Ronald; Ameyan, Wole; et al.
Abstract : Objectives: WHO recommended strengthening the linkages between various HIV prevention programmes and adolescent sexual reproductive health (ASRH) services. The Smart-LyncAges project piloted in Bulawayo city and Mt Darwin district of Zimbabwe established a referral system to link the voluntary medical male circumcision (VMMC) clients to ASRH services provided at youth centres. Since its inception in 2016, there has been no assessment of the performance of the referral system. Thus, we aimed to assess the proportion of young (10–24 years) VMMC clients getting 'successfully linked' to ASRH services and factors associated with 'not being linked'. Design: This was a cohort study using routinely collected secondary data. Setting: All three VMMC clinics of Mt Darwin district and Bulawayo province. Primary outcome measures: The proportion of 'successfully linked' was summarised as the percentage with a 95% CI. Adjusted relative risks (aRR) using a generalised linear model was calculated as a measure of association between client characteristics and 'not being linked'. Results: Of 1773 young people registered for VMMC services, 1478 (83%) were referred for ASRH services as they had not registered for ASRH previously. Of those referred for ASRH services, the mean (SD) age of study participants was 13.7 (4.3) years and 427 (28.9%) were out of school. Of the referred, 463 (31.3%, 95% CI: 30.0 to 33.8) were 'successfully linked' to ASRH services and the median (IQR) duration for linkage was 6 (0–56) days. On adjusted analysis, receiving referral from Bulawayo circumcision clinic (aRR: 1.5 (95% CI: 1.3 to 1.7)) and undergoing circumcision at outreach sites (aRR: 1.2 (95% CI: 1.1 to 1.3)) were associated with 'not being linked' to ASRH services. Conclusion: Linkage to ASRH services from VMMC is feasible as one-third VMMC clients were successfully linked. However, there is need to explore reasons for not accessing ASRH services and take corrective actions to improve the linkages.